Multidimension Analysis of Autonomous Vehicles: The Future of Mobility - Kareem Othman (Civil Engineering Journal, 2021)
The level of investment in AVs technology has been increasing over the years as both researchers and developers are cooperating with the objective of developing AVs and understanding their behaviors and implications. Despite the enthusiastic speculation about AVs, little is known about the implications of AVs on our lives and the intertwined relationships between the implications. Thus, the main objective of this paper is to reveal the benefits and risks of AVs and sketch out the main trends in this area in order to provide some directions and recommendations for the future. This study focuses on analyzing the impact of AVs on the required fleet size, vehicle utilization, cost of mobility, public transit service, public behavior, transportation network, land use, economy, environment, society, and public health. Furthermore, the paper analyzes the intertwined relationship between the implications of AVs. Additionally, the paper sheds light on the potential benefits and challenges of the deployment of AVs in developing countries. The analysis shows that while AVs offer multiple benefits, they also pose new risks. The degree to which AVs can affect our plant mainly depends on regulatory actions, as the broader implications of AVs are mainly dependent on how the technology will be adopted, which can be controlled by regulatory actions. Doi: 10.28991/CEJ-SP2021-07-06 Full Text: PDF